The wheat MYB‐related transcription factor TaMYB72 promotes flowering in rice. Issue 8 (5th February 2016) - Zhang, Lichao; Liu, Guoxiang; Jia, Jizeng; Zhao, Guangyao; Xia, Chuan; Zhang, Lina; Li, Fu; Zhang, Qiang; Dong, Chunhao; Gao, Shuangcheng; Han, Longzhi; Guo, Xiuping; et al.
SUMMARY: Through large‐scale transformation analyses, TaMYB72 was identified as a flowering time regulator in wheat. TaMYB72 is a MYB family transcription factor localized to the nucleus. Three TaMYB72 homologs, TaMYB72‐A, TaMYB72‐B and TaMYB72‐D, cloned from hexaploid wheat were mapped to the short arm of the group 6 chromosomes. Under the long‐day conditions, over‐expression of the TaMYB72 in rice shortened the flowering time by approximately 12 d. Expression analyses suggest that TaMYB72 may function through up‐regulation of florigen genes Hd3a and RFT1 . Abstract : TaMYB72 has been identified as flowering time regulator in wheat. TaMYB72 encoded a MYB family transcription factor localized to the nucleus. Over‐expression of TaMYB72 in rice shortened the flowering time by approximately 12 days. Expression analyses suggested that TaMYB72 may function through the up‐regulation of rice florigen genes Hd3a and RFT1 .